The Effect of the Milling Vial Shape on the In-Situ Consolidation of a Nanocrystalline Al-Li-GNPs Nanocomposite Synthesized by Room Temperature Ball-Milling - Ahmad, Sara I.; Youssef, Khaled M. (Frontiers in Materials, 2022)
Several studies investigating the ball-milling of ductile face-centered cubic (FCC) metals have reported a so-called in-situ consolidation phenomenon where the milled powder is also consolidated during the milling process. Thus, instead of refined powders or agglomerated particles, the formation of spherical bulk particles of the milled material is reported using a combination of cryomilling and room temperature milling processes. In this study, we studied the effect of the milling vial shape on the in-situ consolidation of a graphene nanoplatelets (GNPs) reinforced aluminum-lithium (Al-Li) matrix nanocomposite for the first time. An in-situ consolidated nanometric Al-Li-GNPs nanocomposite with an average grain size of 48 nm and high hardness of 1.48 GPa was attained after only 8 hours of room-temperature milling. The results presented suggest that dense nanostructured composites can be prepared by in-situ consolidation during a one-step milling process and subsequently investigated in order to analyze their mechanical behavior. This allows for the intrinsic mechanical behavior of the synthesized material to be examined without the interference of subsequent high-temperature consolidation processes, thus avoiding unwanted structural changes such as grain growth and second phase formations.